Low prevalence of substance use in people with 22q11.2 deletion syndrome. (November 2019) - Vingerhoets, Claudia; van Oudenaren, Mathilde J.F.; Bloemen, Oswald J.N.; Boot, Erik; van Duin, Esther D.A.; Evers, Laurens J.M.; Fiksinski, Ania M.; Breetvelt, Elemi J.; Palmer, Lisa D.; Vergaelen, Elfi; Vogels, Annick; Meijer, Carin; et al.
Abstract : Background: 22q11.2 deletion syndrome (22q11DS), one of the most common recurrent copy number variant disorders, is associated with dopaminergic abnormalities and increased risk for psychotic disorders. Aims: Given the elevated prevalence of substance use and dopaminergic abnormalities in non-deleted patients with psychosis, we investigated the prevalence of substance use in 22q11DS, compared with that in non-deleted patients with psychosis and matched healthy controls. Method: This cross-sectional study involved 434 patients with 22q11DS, 265 non-deleted patients with psychosis and 134 healthy controls. Psychiatric diagnosis, full-scale IQ and COMT Val 158 Met genotype were determined in the 22q11DS group. Substance use data were collected according to the Composite International Diagnostic Interview. Results: The prevalence of total substance use (36.9%) and substance use disorders (1.2%), and weekly amounts of alcohol and nicotine use, in patients with 22q11DS was significantly lower than in non-deleted patients with psychosis or controls. Compared with patients with 22q11DS, healthy controls were 20 times more likely to use substances in general ( P < 0.001); results were also significant for alcohol and nicotine use separately. Within the 22q11DS group, there was no relationship between the prevalence of substance use and psychosis or COMT genotype. Male patients with 22q11DS were more likely to use substances than female patients with 22q11DS. Conclusions: The results suggest that patients with 22q11DS are at decreased risk for substance use and substance use disorders despite the increased risk of psychotic disorders. Further research into neurobiological and environmental factors involved in substance use in 22q11DS is necessary to elucidate the mechanisms involved. Declaration of interest: None.